Urban form and urban metabolism. Recent research and academic trends conducted at the Lisbon Metropolitan Area - Marat-Mendes, T. (2022)
Urban planning and urban design disciplines have been called to contribute for more sustainable communities. Approaching, describing, and measuring the urban metabolism calls therefore for the most appropriate tools to support the examination of the city from a sustainability point of view. Although prolific contributions have been advanced by the engineering disciplines, mainly in what regards the development of methods to quantify and measure the material flows that operate in the urban system, at the urban design sphere the study of the metabolism remains somehow obscure, delaying the necessary advances to guide the designing of the urban realm and of its necessary infrastructures to promote a sustainable city. This chapter summarises the research process promoted by the author of this manuscript, applied at Lisbon Metropolitan Areas, while promoting the study of the urban metabolism from a visualization perspective, for which the study of urban form proved to be fundamental. To do that, we examine the main contributions of the application of such visualization process, practiced in the past decade at Iscte - Lisbon University Institute, both in two specific financed research projects (MEMO and SPLACH) and at an academic domain, specifically at urban project studios of the Integrated Master of Architecture.